The renewal of epic : responses to Homer in the Argonautica of Apollonius - Knight, Virginia. (Mnemosyne, Supplements, 1995)
The Renewal of Epic considers various modes of allusion to Homer in the Argonautica of Apollonius, dealing not only with similarities in phraseology but also with thematic and structural resemblances. After an introduction, two chapters discuss Apollonian techniques in treating repeated Homeric scenes: sacrifice, shipwreck, boxing and battle. The central section of the work considers the multiple links between the adventures of the Argonauts and Odysseus' wanderings. A final chapter explores Apollonius' innovative treatment of the divine, both generally and in particular scenes. The work shows convincingly that the Argonautica reproduces many of the patterns which have been found in the Iliad and Odyssey . It demonstrates the presence of allusion at every level in the poem, linking it to its predecesors and acting as an essential interpretative aid to the reader.